Evaluation of cowpea accessions for resistance to flower bud thrips (Megalurothrips sjostedti) in Mali - Doumbia, I.Z.; Boukar, O.; Touré, M.; Tamò, Manuele; Salle Tignegre, J.B. de la; Fatokun, C.; Togola, A.; Tongoona, P.B.; Ayertey, J.N. (2019)
Flower bud thrips (Megalurothrips sjostedti) is one of the most damaging pests to cowpea in Africa and varietal resistance is one of the effective approaches to minimize the pest damage. Study was conducted to assess variability among 117 genotypes in addition to two resistant (Sanzisabinli and TVu 1509) and one susceptible (Vita7) checks at Cinzana and N’Tarla locations under natural and artificial infestations of thrips. Parameters such as total number of pods per plant and damage scoring were used to assess the test entries. Genotypes CIPEA82672, Suivita2, TVu 1509 and Sanzisabinli were found highly tolerant, Diaye and TVu7677 moderately tolerant whilst nine genotypes were found tolerant to thrips attacks. CIPEA82672 and Suivita2 had higher grain yield than the resistant checks. Year by genotype, year by location and year by location by genotype interactions were significant for most traits. Genotype by genotype by environment (GGE) effect on yield showed CIPEA82672 most stable across both locations while Suivita2 was only stable at N’Tarla. High broad sense heritability (H2b) was observed for some traits such as damage scoring across locations. Highest genotypic coefficient of variation (GCV) of 81.24 and phenotypic coefficient of variation (PCV) of 75.62 were attributed to total number of pods per plant. Positive correlations were detected between the damage scoring and the number of adult thrips from Cinzana (R2= 0.264) and N’Tarla (R2= 0.603) locations. Confirmation of identified cowpea genotypes highly and moderately tolerant to thrips attacks could be used to improve farmers’ preferred cowpea genotypes susceptible to thrips.